2015
DOI: 10.1093/cercor/bhv288
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Nonadditive Interaction Between Spontaneous and Evoked Activity? Phase-Dependence and Its Relation to the Temporal Structure of Scale-Free Brain Activity

Abstract: The aim of our study was to use functional magnetic resonance imaging to investigate how spontaneous activity interacts with evoked activity, as well as how the temporal structure of spontaneous activity, that is, long-range temporal correlations, relate to this interaction. Using an extremely sparse event-related design (intertrial intervals: 52-60 s), a novel blood oxygen level-dependent signal correction approach (accounting for spontaneous fluctuations using pseudotrials) and phase analysis, we provided di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
172
3
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 97 publications
(191 citation statements)
references
References 88 publications
15
172
3
1
Order By: Relevance
“…2) We did not observe widespread TTV reduction across the entire cortex as previously shown [He, 2013; Huang et al, 2017]. This may be due to the simplicity of the task with lower cognitive load and task demands, as well as a relatively lower number of trials in a sparse-event related design within limited clinical fMRI scanning time.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…2) We did not observe widespread TTV reduction across the entire cortex as previously shown [He, 2013; Huang et al, 2017]. This may be due to the simplicity of the task with lower cognitive load and task demands, as well as a relatively lower number of trials in a sparse-event related design within limited clinical fMRI scanning time.…”
Section: Discussionsupporting
confidence: 57%
“…Each audio clip was followed by inter-trial-intervals (ITIs) ranging unpredictably from 15.5 to 25.5s (2s-step). The benefit of long ITIs was avoiding potential nonlinearities associated with overlapping hemodynamic responses between preceding and subsequent trials, especially for trial-to-trial variability calculation [Huang et al, 2017]. All stimuli were programmed using E-Prime 2.0 (Psychology Software Tools, Pittsburgh, PA) and delivered via an audiovisual stimulus presentation system designed for an MRI environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both regions, we quantified Glx and GABA neurotransmitters, as well as the cerebral spinal fluid (CSF), gray matter (GM) and white matter (WM) content. Also, we computed the regional PLE and the SD, indices of the resting-state temporal structural and variance respectively, as previously described 24,55 (see supplementary methods, supplementary figure 2 and table 1).…”
Section: Mr Sessionmentioning
confidence: 99%
“…22 In the human brain this relationship occurs across a range of timescales and frequencies including infra-slow brain amplitude fluctuations (<0.5 Hz) recorded using functional magnetic resonance imaging (fMRI) during resting wakefulness. 23,24 Recently, we demonstrated that resting-state LRTCs also affect response amplitude to stimuli delivered at a specific phase of spontaneous brain activity (eg, higher LRTC, with larger PLE, amplify response to stimuli delivered at highexcitability phase 24 ). Interestingly, response to multisensory stimuli and multisensory binding are primarily affected by the phase of spontaneous brain activity when stimuli arrive.…”
Section: Introductionmentioning
confidence: 99%